Proceedings of the International Symposium on Mechanical Engineering and Material Science (ISMEMS 2017) 2018
DOI: 10.2991/ismems-17.2018.26
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on optical theoretical models of SiO2 nanofluids

Abstract: Abstract-Photovoltaic and photovoltaic heat technology can be coupled by nanofluid-based solar direct absorption thermal collector. It is an important means to improve the efficiency of comprehensive utilization of solar energy. Nanofluids optical theory plays an important role in the development of new photovoltaic-thermal experimental platform. In addition, study on optical characteristics of nanofluids is still in the initial stage. As a result, it is of great significance for the study of the law and mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Said et al. and Huang et al 39,41 . reported the optical properties like extinction, absorption, and scattering coefficients of nanofluids using Mie scattering and Rayleigh scattering approaches analytically by considering the particle size parameters.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Said et al. and Huang et al 39,41 . reported the optical properties like extinction, absorption, and scattering coefficients of nanofluids using Mie scattering and Rayleigh scattering approaches analytically by considering the particle size parameters.…”
Section: Resultsmentioning
confidence: 99%
“…Said et al and Huang et al 39,41 reported the optical properties like extinction, absorption, and scattering coefficients of nanofluids using Mie scattering and Rayleigh scattering approaches analytically by considering the particle size parameters. Said et al 39 reported a huge difference between experimental and analytical values of optical properties for alumina and TiO 2 nanofluids in the UV region.…”
Section: Absorbancementioning
confidence: 99%
“…Despite the great interest in the thermophysical properties of nanofluids containing SiO 2 , there is lack of information about their optical properties designated in the experimental way. However, in some publications, this topic is presented from the theoretical perspective [39,40]. The obtained results of refractive index, n, analyzed for SiO 2 -EG nanofluids with different concentrations of nanoparticles are summarized in Table 2.…”
Section: Refractive Indexmentioning
confidence: 99%
“…They have also used the Beer-Lambert law to approximate the transmission of light through a layer of nanofluid instead of the MC method. Huang, Bai and Luo Huang, Bai and Luo [16] have also investigated the theoretical optical properties of silicon dioxide nanoparticles using Mie's theory. Their modelling approach is similar to that of Tan et al [17], but Huang, Bai and Luo [16] have included the properties obtained using the Rayleigh scattering model, which assumes that the size of the nanoparticles are much smaller than the wavelength of incident radiation.…”
Section: Theoretical Computation Of Radiative Propertiesmentioning
confidence: 99%
“…Using Eqs. (16)(17)(18)(19), the properties of the nanofluid may be found by combining the properties of the base fluid and the nanoparticles. The equations below apply.…”
Section: Radiative Properties Of Nanofluidmentioning
confidence: 99%